2000
DOI: 10.1002/1099-0801(200010)14:6<406::aid-bmc31>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Hyphenated chromatographic methods for biomaterials

Abstract: The improvement in hyphenated analytical techniques has significantly widened their applications to the analysis of biomaterials. In this article, we discuss recent advances in applications of hyphenated chromatographic techniques including capillary electrophoresis to the analyses of biological samples. As tools of separation, gas chromatography, high-performance liquid chromatography and capillary electrophoresis are considered with special emphasis on applications utilizing the hyphenation of these methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…DIB-Cl, an easy-to-prepare 17 reagent which is stable 18 in acetonitrile solution for at least 1 month when kept in the dark at room temperature, was previously successfully applied as a fluorescent pre-column reagent for sympathomimetic amines. In the present study, DIB-Cl was also found to be applicable as a fluorescent derivatization reagent for Phe, Cre and Xyls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DIB-Cl, an easy-to-prepare 17 reagent which is stable 18 in acetonitrile solution for at least 1 month when kept in the dark at room temperature, was previously successfully applied as a fluorescent pre-column reagent for sympathomimetic amines. In the present study, DIB-Cl was also found to be applicable as a fluorescent derivatization reagent for Phe, Cre and Xyls.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few fluorescent derivatization reagents have been developed for this purpose. [14][15][16] In a previous paper, we reported the synthesis of a new HPLC-fluorescence derivatization reagent for amines and phenols, 17 i.e., 4-(4,5-diphenyl-1H-imidazol-2-yl)benzoyl chloride (DIB-Cl), and applied it to the determination of sympathomimetic amines 18 and chlorophenols. 19 In this study, DIB-Cl was applied to determine Phe, Cres and Xyls in urine to confirm its applicability to a wide variety of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the ideal detector for liquid chromatography have been summarized by Lemiere [ 103], and several fundamental reviews on this topic have also been published in recent years [104][105][106][107][108]. The major features of an effective detector are: selectivity, specificity, sensitivity, stability, and linearity.…”
Section: Detectorsmentioning
confidence: 99%
“…Two-dimensional LC (2D-LC) is now being applied more and more in high-resolution separations. 10) [ 147]. Due to technical difficulties, 2D-electrophoresis still cannot achieve the reproducibility required for unambiguous comparison of two independent separations.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…To date, many reviews describing the labeling reagents for HPLC have been published. [4][5][6][7][8] Among medicaments, many kinds of drugs have been widely abused and such abuse has caused serious social problems worldwide. For instance, methamphetamine (MP) is the most popular abused drug in Japan.…”
Section: Introductionmentioning
confidence: 99%